China's Christianity : from missionary to indigenous church - Clark, Anthony E. (Studies in Christian Mission, 2017)
Among the assumptions interrogated in this volume, edited by Anthony E. Clark, is if Christianity should most accurately be identified as "Chinese" when it displays vestiges of Chinese cultural aesthetics, or whether Chinese Christianity is more indigenous when it is allowed to form its own theological framework. In other words, can theological uniqueness also function as a legitimate Chinese Christian cultural expression in the formation of its own ecclesial identity? Also central to what is explored in this book is how missionary influences, consciously or unconsciously, introduced seeds of independence into the cultural ethos of China's Christian community. Chinese girls who pushed "the limits of proper behaviour," for example, added to the larger sense of confidence as China's Christians began to resist the model of Christianity they had inherited from foreign missionaries. Contributors are: Robert E. Carbonneau, CP, Christie Chui-Shan Chow, Amanda C. R. Clark, Lydia Gerber, Joseph W. Ho, Joseph Tse-hei Lee, Audrey Seah, Jean-Paul Wiest, and Xiaoxin Wu.